Small mammal communities, associated damage to rice and damage prevention in smallholder rice storage facilities in Sri Lanka - Htwe, Nyo Me; Sarathchandra, Siriwardana Rampalage; Sluydts, Vincent; Nugaliyadde, Lionel; Singleton, Grant R.; Jacob, Jens (Elsevier, 2021)
Several rodent species damage rice crops and commensal rodents cause damage to stored produce and infrastructure, hygienic problems and they can transmit zoonotic pathogens. In the first such study in Sri Lanka, we identified the main rodent and shrew species and the extent of post-harvest damage caused in rice storage facilities of smallholder farmers. Netting of rice bags was trialled as a new measure of protection. Field experiments were performed in the three main agro-ecological zones of Sri Lanka. Five rodent species and one shrew species were captured in storage facilities. Rattus rattus, Bandicota indica and Suncus murinus were the dominant species in storage facilities. The small mammal composition was more related to season than to region. In storage, depending on region, 3.2–9.1% (mean 7.6%) of rice was lost to rodents when rice was stored indoors in unprotected polyethylene bags. Netting around bags reduced damage by 89% - equivalent to the annual rice consumption of one person per storage facility, reduced the presence of rodent droppings by 92% and the bag area damaged by rodents by 96%. Our findings clearly show the considerable amount of damage caused by rodents to rice post-harvest across three agro-ecological zones of Sri Lanka and indicate that netting bags considerably reduces damage and contamination. This netting can be used to aid the development of an ecologically-based rodent management (EBRM) program tailored to local conditions. More detailed studies are needed to fully understand the population and breeding ecology of the relevant rodent pest species in relation to damage patterns to optimize management beyond individual structural measures.